2013
DOI: 10.1007/s00005-013-0235-0
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria as Oxidative Signaling Organelles in T-cell Activation: Physiological Role and Pathological Implications

Abstract: Early scientific reports limited the cell biological role of reactive oxygen species (ROS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 221 publications
(265 reference statements)
1
56
0
Order By: Relevance
“…In this context, Sena et al showed that ETC complex III-originating ROS, produced upon T-cell activation, are essential for NFAT activation as well as IL-2 production (Murphy and Siegel, 2013;Sena et al, 2013). The findings of Sena et al are in line with a study by Kaminski and colleagues who, a few years earlier, reported that complex-I-oxidants control IL-2 and IL-4 production and activation of NF-κB and AP-1 (Kaminski et al, 2010(Kaminski et al, , 2013. The authors of the latter study further supported their conclusions by examining T cells isolated from atopic dermatitis patients.…”
Section: When and Where Are Ros Generated?supporting
confidence: 68%
See 2 more Smart Citations
“…In this context, Sena et al showed that ETC complex III-originating ROS, produced upon T-cell activation, are essential for NFAT activation as well as IL-2 production (Murphy and Siegel, 2013;Sena et al, 2013). The findings of Sena et al are in line with a study by Kaminski and colleagues who, a few years earlier, reported that complex-I-oxidants control IL-2 and IL-4 production and activation of NF-κB and AP-1 (Kaminski et al, 2010(Kaminski et al, , 2013. The authors of the latter study further supported their conclusions by examining T cells isolated from atopic dermatitis patients.…”
Section: When and Where Are Ros Generated?supporting
confidence: 68%
“…The authors of the latter study further supported their conclusions by examining T cells isolated from atopic dermatitis patients. Blockade of mitochondrial complex-I in these cells reduced disease-associated hyper-expression of IL-4 (Kaminski et al, 2010(Kaminski et al, , 2013. In addition, a number of recent studies identified novel molecular players, which all affect mitochondrial ROS production and thereby T-cell activation as well as apoptosis (Kaminski et al, 2007(Kaminski et al, , 2013Silic-Benussi et al, 2010).…”
Section: When and Where Are Ros Generated?mentioning
confidence: 98%
See 1 more Smart Citation
“…However, if immune system either fails to be properly activated or is persistently activated it can contribute to multiple diseases including autoimmunity, cardiovascular disease, and accelerate the normal aging process. In the past two decades, there is substantial evidence that ROS are essential second messengers in innate and adaptive immune cells [73, 74]. Yet, increased levels of ROS within immune cells can result in hyperactivation of inflammatory responses resulting in tissue damage and pathology [75].…”
Section: Redox Signaling and Oxidative Stress: Regulation Of Inflammamentioning
confidence: 99%
“…Mitochondria are indeed involved in apoptosis induction during activation-induced cell death caused by TCR stimulation and aimed at restricting further clonal expansion to prevent autoimmune disorders [35,36]. Finally, mitochondria produce ROS, which accompany upregulation of nuclear factor kappa B (NFκB) and nuclear factor of activated T cells (NFAT), two master regulators of TCR-stimulated transcription changes [3741]. These three processes are stimulated by an increase in mitochondrial Ca 2+ , as this ion stimulates the tricarbon acid (TCA) cycle in the mitochondrial matrix, leading to an increase in proton pumping, ATP synthesis and ROS production [42,43] (figure 1).…”
Section: Introductionmentioning
confidence: 99%